Higher education waqf: implementation model for a private higher education / Baharuddin Sayin ...[et al.] - Sayin, Baharuddin; Mat Rani, Mohd Afandi; Ab Hamid, Muhammad Hamizan; Ab. Manan, Siti Khadijah (Academy of Contemporary Islamic Studies (ACIS), 2016)
Higher education waqf is an important tool in developing knowledgeable intellectuals. The fact that many renowned universities around the globe that are waqf-based has proven its importance. Higher education institutions like AlAzhar University have successfully produced many renown scholars and intellectuals that no one could dispute. In Malaysia, serious attention on benefitting higher education waqf is heightened and a number of higher institutions are now operating based on waqf. One such example is University College Bestari (UCB) in Terengganu Malaysia. This case study examined the historical background, the development of waqf asset, contribution and beneficial distribution of waqf property as well as the challenges and prospects of UCB. It is found that UCB has successfully expanded the waqf funds through the waqf scheme of land lot by getting approval from the Terengganu Islamic Religious and Malay Customs Council (MAIDAM). The implementation of educational waqf by UCB can be a model to other educational institutions in developing waqf property and generating revenue.